2010
DOI: 10.1021/ja9100084
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Modification of Au via Treatment with Piranha Solution Provides Low-Pd Releasing and Recyclable Pd Material, SAPd

Abstract: We have found in the SR-HXPS measurement of Piranha-treated Au(111)/mica that the gold surface underwent sulfur modification during this treatment, which was believed to have only removed impurities from the gold surface. We also successfully developed a practical Pd material, SAPd, whose Pd was immobilized on sulfur-modified Au. With the lowest Pd-releasing levels and high recyclability, this is one of the best Pd materials thus far developed. Because it leaches extremely low levels of Pd into reaction mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(39 citation statements)
references
References 19 publications
3
36
0
Order By: Relevance
“…As reported in our previous research, [17][18][19][20][21][22][23][24][25][26][27] SAPd absorbs very few organic compounds and can therefore be used in combinatorial synthesis because of its small surface area. It was envisaged that SGlPd would perform in a similar manner to SAPd.…”
Section: Liquid-phase Combinatorial Experimentsmentioning
confidence: 56%
See 2 more Smart Citations
“…As reported in our previous research, [17][18][19][20][21][22][23][24][25][26][27] SAPd absorbs very few organic compounds and can therefore be used in combinatorial synthesis because of its small surface area. It was envisaged that SGlPd would perform in a similar manner to SAPd.…”
Section: Liquid-phase Combinatorial Experimentsmentioning
confidence: 56%
“…Organic materials containing sulfate and xylene as the major ingredients are distributed between the Pd nanoparticles, allowing for the formation of stable high-density PdNPs without condensation. [17][18][19][20][21][22][23][24][25][26][27] The results of the XANES analysis suggest that the oxidized sulfur preserves the structure of the PdNPs in SGlPd as well as SAPd.…”
Section: mentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, Arisawa et al [6,7] found that SO 4 exist on gold surfaces after a Piranha treatment [8] during a process of making a Pd catalyst. The Piranha treatment had been traditionally used to remove organic residues from gold surfaces [9][10][11][12][13][14] and to make self-assembled monolayers (SAMs) of alklthiols (RSH) on metal surfaces [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, h-BN is cheaper than gold. It means that Pd and SO 4 on h-BN is a promising candidate substrate for catalysts like SAPd[6,33,35], Pd and SO 4 on gold substrate for the SuzukiMiyaura coupling reactions…”
mentioning
confidence: 99%